The ℓ-translativity of Abel-type matrix - Mulatu Lemma (International Journal of Mathematics and Mathematical Sciences)
Lemma introduced the Abel-type matrix Aα,t defined by ank=(k+α    k)tnk+1(1−tn)α+1, where α>−1, 0<tn<1, for all n, and limtn=1; and studied it as mappings into ℓ. In this paper, we extend our study of this matrix and investigate its translativity in the ℓ-ℓ setting.